Dietary transition and its relationship with socio-economic status and peri-urban obesity - Anjali Purushotham; Anaka Aiyar; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2021)
In 2015-16, India was the seventh-largest economy in the world and had more than 200 million people at risk for obesity. Overconsumption of calories from processed foods, an outcome of a country's dietary transition, is known to be an important mechanism that drives risks for obesity. Testing the relationship between processed foods, socio-economic status and obesity has not been possible thus far due to the limited availability of relevant micro-level data. In this paper, we use novel cross-sectional data from a primary socio-economic survey conducted in the rural-urban interface of Bangalore, a mega-city in India, to explore the role of dietary transition in obesity. We show that calories from semi- and ultra-processed foods are positively associated with the prevalence of obesity (Body Mass Index, BMI, =25) among women. Households in the lower-income group are at higher risk of obesity due to excess consumption of calories from semi-processed foods while ultra-processed foods are associated with obesity among higher income groups. We also find that excess consumption of semi-processed food calories is strongly associated with an increase in the prevalence of obesity among women who meet their recommended dietary allowance for calories. This suggests that there is a threshold effect before which consumption of calories from processed foods may improve BMI. Furthermore, in line with the literature, we show that labor-intensive physical activities seem to alleviate the effect of calories on obesity. The strength of the association between semi-processed foods and obesity reduces with occupations association with greater physical activity. Our study highlights how diet-related transitions during economic growth and urbanization impact different economic groups & the dual burden of malnutrition. Our results call for strategic interventions, that are focused on reducing obesity in India, to work on moderating the consumption of semi-processed foods among peri-urban households.
Keywords: 330; Obesity; dietary transition; structural transformation; rural-urban interface; urbanization; India